(untitled) (Journal of the College of Basic Education, 2022)
The current study aims to remove organic pollutants (phenol) from industrial effluent using batch adsorption on activated carbon and Iraqi porcelanite rocks, and also to compare the removal efficiency of phenol for both adsorbents. Batch mode adsorption experiments were performed by varying different fractional size of adsorbent. The obtained results indicated that the adsorption of phenol increases with decreasing particle size of adsorbent. It seems that activated carbon with 45 µm particle size is more effective in removal of phenol than Iraqi porcelanite rocks powder of the same particle size. The results also proved that the activated carbon has the ability to remove organic pollutant (phenol) more efficient than Iraqi porcalenite rocks. In addition, the adsorption data fit vary well with freundlich model of adsorption isotherm